Pengelolaan Daun Kering untuk Pupuk Kompos - Pakpahan, Enni Halimatussa'diyah; Dwi, Citra Partika; Balqis , Zia Syamsiah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
A material given to plants to increase nutrient availability is called fertilizer. This research project aims to find a solution to the environmental pollution problem caused by the accumulation of dry leaf litter. Compost is made using dry leaf litter waste as the main component and EM4 as an aid. EM4 is responsible for breaking down the organic material in the leaves. The finished dry leaf compost is odorless, in the form of loose granules, has a brittle and somewhat rough texture, and is dark brown in color. The research method used is literature research, or research derived from books and print journals accessible on Google Scholar. This type of research uses descriptive studies and several works of researchers with relevant fields of study. Data collected through inductive methods are then analyzed using one or more initial data sets. The obtained data is examined using a descriptive analytical approach. By transforming dry leaves into more useful and economically valuable compost, this research also aims to develop and enhance the creative abilities of the community and the local economy. Bright colors indicate composting that is too dry or moisture levels below 30%. One determining factor of compost maturity is its aroma. The compost fermentation process will produce various strong aromas.